KONSEKUENSI HUKUM PENIMBUNAN MASKER DAN TABUNG OKSIGEN DI MASA PANDEMI COVID-19 - Reyno Iksan Derizky; I Made Sarjana (Kertha Negara : Journal Ilmu Hukum, 2023)
The purpose of this article is to find out and analyze the legal provisions and instruments for mask and oxygen tube stockpiling actions during the pandemic COVID-19 as well as finding out the legal sanctions or accountability for mask and oxygen tube stockpiling actions during the pandemic COVID-19. This article uses normative legal research that uses statutory and comparative approach. Based on the results of the analysis, it is known that legal provisions and instruments for mask and oxygen tube stockpiling actions during the pandemic COVID-19 are contained in Pasal 29 ayat (1) Undang-Undang Nomor 7 Tahun 2014 tentang Perdagangan, Pasal 4 and 5 Undang-Undang Nomor 5 Tahun 1999 tentang Larangan Praktek Monopoli dan Persaingan Usaha Tidak Sehat, and Pasal 12 Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen. If a business actor is found to have committed an act of stockpiling mask and oxygen tube during pandemic COVID-19, the business actor may be subjected to administrative and criminal sanctions as regulated in Undang-Undang Nomor 7 Tahun 2014 tentang Perdagangan and Undang-Undang Nomor 5 Tahun 1999 tentang Larangan Praktek Monopoli dan Persaingan Usaha Tidak Sehat. Keywords: Stockpiling, Trade Competition, Monopoly